Elite women`s football: Evolution and challenges for the years ahead - Nassis, G. P.; Brito, J.; Tomás, R.; Heiner-Møller, K.; Harder, P.; Okholm Kryger, K.; Krustrup, P. (Scandinavian Journal of Medicine & Science in Sports, 2022)
The aim of this editorial was to discuss challenges that women's football may face in the short and the longer term. The realization of such challenges will allow practitioners and scientists to work more effectively in finding solutions to overcome them.